Tri-ponderal mass index vs. body mass index to determine obesity and central obesity in adolescents - Moelyo, Annang Giri; Ferdian, Hanum (Paediatrica Indonesiana, 2024)
Background Tri-ponderal mass index (TMI) is as accurate as body mass index (BMI) in predicting body fat in children and adolescents. Despite TMI simplicity, there have been few studies comparing the sensitivity and specificity of TMI and BMI in determining obesity and central obesity in adolescents. Objective To compare the sensitivity and specificity of TMI and BMI in determining general obesity and central obesity in adolescents. Methods This cross-sectional study was conducted in Surakarta. Healthy school children aged 12 to 17 years underwent TMI, BMI, and waist circumference measurements in 2016, 2017, 2019. Tri-ponderal mass index was calculated as the weight divided by the height in metres cubed (kg/m3). General obesity was defined by the International Obesity Task Force (IOTF) classification of overweight-obese. The BMI-WHO overweight/obesity was defined as over the 85th percentile of the BMI SDS (WHO growth reference). Central obesity was defined as waist-to-height ratio (WtHR) ? 0.5. The sensitivity and specificity of TMI and BMI were calculated. Results A total of 1,173 children and adolescents (837 girls, 336 boys) aged 12-17 years were recruited into this study. The overall prevalences of obesity by BMI-WHO, TMI, BMI-IOTF, and WtHR were 22.68%, 14.92%, 20.55%, and 32.74%, respectively. The sensitivity of BMI-WHO vs. TMI for general obesity was 100.00% vs. 77.71%, respectively (girls) and 100.00% vs. 59.52%, respectively (boys). The specificity was 98.24% vs. 99.56%, respectively (girls) and 98.84% vs. 100%, respectively (boys). The sensitivity of BMI-WHO vs. TMI for central obesity was 58.77% vs 48.82%, respectively (girls), and 47.40% vs 27.75%, respectively (boys). The specificity was 92.81% vs. 96.49%, respectively (girls), and 90.80% vs 98.77%, respectively (boys). Conclusion Tri-ponderal mass index consistently showed higher specificity and lower sensitivity than BMI in assessing general and central obesity.